Provincializing the Western literary canon - Charon, Mylene (HAL CCSD, 2023)
International audience This paper argues that the novel After Story, published in 2021 by Eualeyai and Kamillaroi writer Larissa Behrendt, practices intellectual sovereignty as a form of what Dipesh Chakrabarty calls "anti-colonial gratitude" (Provincializing Europe, p. 255). With its Australian First Nations characters who travel to England on a literary tour and finally decide to become writers of their own ancestral stories, it deploys intertextuality in a decolonial way. Intertextuality, which is a relational literary device, is thus operationalized to claim a plural genealogy of thought - one where First Nations people's ways of being in the world, of knowing or of telling stories, such as the characters' Elder Aunty Elaine, are legitimate. Engaging in a critical relationship with the Western canon has the effect of “provincializing” it; that is to locate it in Europe and to challenge its claims to universalism. As a result, not only does the novel enter in a critical, anti-colonial, relationship with the Western literary canon but, at the same time, it centers First Nations’ knowledges and storytellers. Cette communication défend l'idée que le roman After Story, publié en 2021 par l'autrice Eualeyai et Kamillaroi Larissa Behrendt, exerce sa souveraineté intellectuelle comme une forme de "gratitude anti-coloniale" ( Dipesh Chakrabarty, Provincializing Europe, p. 255). Avec ses personnages australiens des Premières Nations qui effectuent un voyage littéraire en Angleterre et finissent par décider de devenir écrivaines de leurs propres histoires ancestrales, le roman déploie l'intertextualité de manière décoloniale. Dispositif littérature relationnel, l'intertextualité est ainsi utilisée pour revendiquer une généalogie de pensée plurielle, où les manières d'être au monde, de connaître et de raconter des peuples des Premières Nations sont aussi légitimes. La relation critique avec le canon occidental a pour effet de le provincialiser, c'est-à-dire de le situer en Europe et de remettre en question ses ...